(untitled) (Educational Empowerment Journal, 2024)
Although review redundancy is still understudied, it may be a typical teaching strategy in Southeast Asian and Indonesian institutions. This paper, which employs a subjective case study methodology, is based on interviews with administrators and instructors from several Jakarta, Indonesian schools in arrange to way better get it the components and results related with rehash testing. The results show that understudies who participate seldom, are from low-income households, are older, or are confined to residential labor at home are more likely to repeat a review. A few effective practices that teachers suggest to advance the sufficiency of review redundancies include modifications to instructing strategies, classroom formats, and openings for understudy inclusion